REACTIONS TO AMY COHEN - Prado, Mariana Mota; Trebilcock, Michael J. (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
In this fascinating analysis of our book, Amy Cohen raises a series of interesting and challenging questions. In focusing solely on means, has the concept of institutional bypasses obscured normative disputes about the ends? In rejecting any form of illegality, isn’t the concept of bypass implicitly assuming a concept of legitimacy that needs to be unpacked? Also, in trying to separate public and private initiatives, has the bypass potentially ignored complex interactions between market initiatives and governmental regulations? Cohen provides concrete examples to illustrate the real-world policy implications of these questions.